2022
DOI: 10.1186/s12885-022-09437-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and RNA-related molecular markers of trastuzumab-chemotherapy-associated cardiotoxicity in HER2 positive breast cancer: a systematic review

Abstract: Cancer-therapy related cardiotoxicity (CTRCT) is a significant and frequent complication of monoclonal antibody directed therapy, especially Trastuzumab, for human epidermal growth factor receptor 2 (HER2) overexpressing breast cancers. Reliable, clinically available molecular predictive markers of CTRCT have not yet been developed. Identifying specific genetic variants and their molecular markers, which make the host susceptible to this complication is key to personalised risk stratification. A systematic rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 55 publications
(63 reference statements)
0
18
0
Order By: Relevance
“…These factors are likely the reason why the level of adverse cardiac events is closely balanced across the age groups. Further study needs to investigate other possible risk factors for chemotherapy-induced cardiotoxicity, such as genetic factors [ 19 ]. These risk factors, along with the changes regarding hypertension and trastuzumab use we have proposed, should be included in any future risk scoring methods.…”
Section: Discussionmentioning
confidence: 99%
“…These factors are likely the reason why the level of adverse cardiac events is closely balanced across the age groups. Further study needs to investigate other possible risk factors for chemotherapy-induced cardiotoxicity, such as genetic factors [ 19 ]. These risk factors, along with the changes regarding hypertension and trastuzumab use we have proposed, should be included in any future risk scoring methods.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, the most predominant idea about the malignant transformation of breast tissue has been attributed to changes in genetic structure, which may be due to epigenetic [46][47][48] or genetic effects per se 49,50 . These changes generate a process that alters the synthesis of proteins, their behavior and therefore the signaling around the tissue, from a biochemical and molecular point of view 51,52 .…”
Section: Discussionmentioning
confidence: 99%
“…A genome wide association study (GWAS) carried out in 481 patients with (11 cases) and without (257 controls) trastuzumab-induced cardiotoxicity in Japanese showed that five SNPs including rs9316695, rs28415722, rs7406710, rs11932853, and rs8032978 were independent predictors of trastuzumab cardiotoxicity ( P combined = 7.82 × 10 −15 , OR = 40.0) ( 47 ). The HER-2 SNPs Ile654Val (rs1801201), Ile655/Val (rs1136201), and Pro1170Ala (rs1058808) were also associated with susceptibility to cardiotoxicity ( 48 ). In a meta-analysis of 344 patients with 43 developed drug induced cardiotoxicity, 67% of the patients carried the Ile/Val genotype, resulting in an OR of 5.35.…”
Section: Pharmacogenomics In Dictmentioning
confidence: 99%
“…In a meta-analysis of 344 patients with 43 developed drug induced cardiotoxicity, 67% of the patients carried the Ile/Val genotype, resulting in an OR of 5.35. HER-2 Ile655Val is an independent predictor of cancer-therapy related cardiotoxicity ( 24 , 48 ). By comparing HER-2 genotype distribution in 29 cases with cardiotoxicity and 111 controls underwent trastuzumab treatment, Stanton et al, observed association between Pro1170Ala polymorphism and increased risk of trastuzumab induced cardiomyopathy ( 49 ).…”
Section: Pharmacogenomics In Dictmentioning
confidence: 99%